PENGARUH RETURN ON ASSET, PRICE EARNING RATIO, EARNING PER SHARE, DEBT TO EQUITY RATIO DAN PRICE TO BOOK VALUE TERHADAP HARGA SAHAM PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BEI - Adam Satria Widyanto, 09.05.52.0076; Susilowati, Yeye (Students Journal of Accounting and Banking, 2014)
This study aimed to examine the effect of Return on Assets ( ROA ), Price Earning Ratio ( PER ), Earning Per Share ( EPS ), Debt To Equity Ratio ( DER ), and price to book value ( PBV ) of the stock price of companies included in LQ - 45 categories listed in Indonesia Stock Exchange IDX. The population is the entire company LQ - 45 In Indonesia Stock Exchange ( IDX ) with 45 companies and penlitian during the period 2009 to 2012. Samples taken in this study were as many as 26 companies. The sampling technique was purposive sampling. Analysis tools used in this research are Linear Regression Analysis. The results showed that the coefficient of determination in this study is the value of Adjusted R Square of 95.9 %. While the test statistic f -test shows that the Return on Assets ( ROA ), Price Earning Ratio ( PER ), Earning Per Share ( EPS ), Debt To Equity Ratio ( DER ), and price to book value ( PBV ) jointly influence significant impact on stock prices. Partial hypothesis test results showed that there is a positive effect between price earning ratio ( PER ) Earning Per Share ( EPS ) Debt To Equity Ratio ( DER ) and price to book value ( PBV ) on stock prices. As for the Return on Assets ( ROA ) showed a negative influence on stock prices.Keywords: Return on Assets ( ROA ), Price Earning Ratio ( PER ) , Earning Per Share ( EPS ), Debt To Equity Ratio ( DER ), and Price to Book Value ( PBV ) and Stock Price